Pemikiran Ibnu Khaldun tentang Pendidikan Islam di Era Artificial Intelligence - Maratul Azizah; Teguh Hadi Wibowo; Joko Susilo (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2026)
The development of Artificial Intelligence (AI) in education offers efficiency, personalization, and adaptive learning, but also presents challenges related to reduced critical thinking, moral value internalization, and social interaction. This study analyzes the relevance of Ibn Khaldun’s educational thought in the Muqaddimah to address the challenges of education in the AI era. A qualitative approach was used through literature review and historical analysis of Ibn Khaldun’s concepts, including gradual learning (tadarruj), habituation (malakah), the development of three levels of intellect (al-‘aql al-tamyiz, al-‘aql al-tajribiy, al-‘aql al-nadzari), and the strategic role of educators as moral exemplars and value facilitators. The findings indicate that Ibn Khaldun’s principles can serve as a normative framework for integrating AI in education, ensuring that technology functions as a supporting tool (wasīlah), rather than replacing the educator’s role. Implementation strategies include a holistic and adaptive curriculum, value internalization through repeated practice, moral guidance by educators, AI-based adaptive learning models, and a balance between technology and humanism. This approach allows learners to develop as insān kāmil, fully balanced intellectually, morally, socially, and spiritually. The results underscore the importance of combining technological innovation with humanistic educational principles to cultivate competent, ethical, and well-rounded learners in the digital era.